The evolutionary and disruptive potential of Industrie 4.0 - Winter, Johannes (Hungarian Geographical Bulletin, 2020)
Despite all the hype, digitalization is not a new trend. The third industrial revolution started as early as the beginning of the 1970s and has continued to this day. It is shaped using electronics and information technologies (IT) in the economy and progressive standardization and automation of business processes. While exponential growth is typical for the IT sector, this is rarely the case for the classic industries. For a long time, the change was barely perceivable, which led many players to denounce these developments as uninteresting, losing interest at an early stage. But then, as the process picks up breakneck speeds, it often becomes impossible to jump on board or keep up. When automation driven by electronics and IT established itself in production, it led to dramatic changes in value chains and employment structures. Through standardization and automation, business processes became more efficient, quicker, and transparent. When the dot-com speculative bubble burst in 2000, vending machines that ordered supplies independently were already in operation. In the search for the business model of the Information Age, electronic marketplaces became popular pioneers for dynamic business networks and real-time business. Many of today’s well-known technology firms – such as Google, Netflix, or the predecessors of Facebook – were already active on the market in a similar form. In recent years a second wave of digital transformation is experienced and with it, a fourth industrial revolution. The necessary information and communication technologies have now become so cost-effective that they can be used in widespread areas. As a result, many of the dot-com promises have been realized today. The aim of this paper is to intensify the Industrie 4.0 debate in economic geography by showing the evolutionary and disruptive potential of Industrie 4.0.